The Roles of Social Media Influencers on Online Fundraising in Indonesia - Joyce Cheah Lynn-Sze; Nurul Nazielah Bt Fathi (Journal of Indonesian Economy and Business, 2023)
Introduction/Main Objectives: Using celebrities for online fundraising has become increasingly popular, especially duringthe recent COVID-19 pandemic. It has encouraged social media influencers (SMIs) around the world to help raise money through their own Instagram accounts. Thus, this study aims to understand the roles of SMIs in fundraising activities, to identify the influencers’ attributes which affect their followers’ willingness to donate, and to explore the motivation of the followers to donate. The SMI who became the subject of this study is Rachel Vennya, an Instagram celebrity who is also an entrepreneur. Background Problems: The growing role of SMIs in online fundraising has indirectly made them idols. However, there is a need to investigate what drives social media users’ willingness to support and donate to online fundraising hosted by SMIs. Novelty: This study enriches the literature about SMIs and the motivation to donate in different contexts, such as online fundraising through Instagram, especially amid the COVID-19 pandemic in Indonesia. Research Methods: Using a qualitative method, semi-structured interviews with 10 informants, who were aged between 25 and 35 years old were conducted. The informants were selected from among Rachel Vennya’s Instagram followers and participated in her COVID-19 fundraising campaign. Finding/Results: In accordance with the objectives, there are three roles for the SMIs, which are expanding their followers, raising awareness and inspiring people to donate. The findings also identified three characteristics that affect the willingness of people to donate, namely attractiveness, trustworthiness and ability, while the influencer’s influence and making it easy to donate are the motivations for the followers’ intentions to donate. Conclusion: The findings could contribute to the knowledge of SMIs and online fundraising. They could also help the governments’ efforts to get non-profit organizations to focus attention on proactive strategies aimed at boosting their online fundraising campaigns in the future.